Neuromodulation of inhibitory synaptic transmission in the basolateral amygdala during fear and anxiety - Fu, Xin; Tasker, Jeffrey G. (Frontiers in Cellular Neuroscience, 2024)
The basolateral amygdala plays pivotal roles in the regulation of fear and anxiety and these processes are profoundly modulated by different neuromodulatory systems that are recruited during emotional arousal. Recent studies suggest activities of BLA interneurons and inhibitory synaptic transmission in BLA principal cells are regulated by neuromodulators to influence the output and oscillatory network states of the BLA, and ultimately the behavioral expression of fear and anxiety. In this review, we first summarize a cellular mechanism of stress-induced anxiogenesis mediated by the interaction of glucocorticoid and endocannabinoid signaling at inhibitory synapses in the BLA. Then we discuss cell type-specific activity patterns induced by neuromodulators converging on the Gq signaling pathway in BLA perisomatic parvalbumin-expressing (PV) and cholecystokinin-expressing (CCK) basket cells and their effects on BLA network oscillations and fear learning.